2000
DOI: 10.1046/j.1365-2230.2000.00711.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical sucralfate in the management of peristomal skin disease: an open study

Abstract: Dermatoses affecting the skin around stoma sites are common and difficult to treat. We have investigated the effectiveness of topical sucralfate in the management of peristomal dermatoses in adults using an open study design. Apart from forming a physical barrier to further irritation, sucralfate binds to basic fibroblast growth factor preventing its degradation and thereby promotes healing. In eight out of nine patients with faecal or urine erosions, daily, topical sucralfate treatment was associated with hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 13 publications
(13 reference statements)
0
21
0
Order By: Relevance
“…The sporadic studies and case reports available in the literature were all coherent indicating the favorable effect of topical sucralfate in wound repair and in skin protection. Topical sucralfate has been successfully studied in peristomal and perineal dermatoses, in moist desquamation during radiotherapy, in erosion and ulceration of the perineal area, in vaginal ulceration, in dystrophic epidermolysis bullosa, in second and third degree burns, and in a pilot trial with non-healing, full-thickness venous stasis ulcers refractory to 8 weeks of conventional therapy (19)(20)(21)(22)(23)(24)(25)(26)(27). The main objective of this study was to determine the effectiveness, safety and tolerability of the local treatment of chronic wounds with a sucralfate gel (SUC-LIS 95).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sporadic studies and case reports available in the literature were all coherent indicating the favorable effect of topical sucralfate in wound repair and in skin protection. Topical sucralfate has been successfully studied in peristomal and perineal dermatoses, in moist desquamation during radiotherapy, in erosion and ulceration of the perineal area, in vaginal ulceration, in dystrophic epidermolysis bullosa, in second and third degree burns, and in a pilot trial with non-healing, full-thickness venous stasis ulcers refractory to 8 weeks of conventional therapy (19)(20)(21)(22)(23)(24)(25)(26)(27). The main objective of this study was to determine the effectiveness, safety and tolerability of the local treatment of chronic wounds with a sucralfate gel (SUC-LIS 95).…”
Section: Discussionmentioning
confidence: 99%
“…The sporadic studies and case reports available in the literature are all consistent, indicating the favorable effect of topical sucralfate in wound repair and in skin protection. Almost all studies indicated the safe and effective behaviour of this compound (19)(20)(21)(22)(23)(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…Surgical treatment with stoma relocation is associated with a high chance of recurrence, but stoma closure has been associated with no recurrence . Recent studies showed promising results with newer therapies such as cultured keratinocyte autografts, topical sucralfate, topical crushed prednisone, and biologic treatment …”
Section: Preexisting Skin Diseases Account For Approximately 20% Of Pmentioning
confidence: 99%
“…55 Recent studies showed promising results with newer therapies such as cultured keratinocyte autografts, topical sucralfate, topical crushed prednisone, and biologic treatment. [56][57][58][59] Koebnerization and other skin diseases Psoriasis and vitiligo both can be seen in periostomal skin because of repeated trauma (Fig. 7).…”
Section: Fungal Infectionmentioning
confidence: 99%
“…11 It has been demonstrated that sucralfate binds to basic fibroblast growth factor preventing its degradation and thereby promoting healing. 12,13 We postulated that all of these characteristics of sucralfate could be harnessed for improving healing of the hemorrhoidectomy wounds. This study was designed to examine the influence of topical sucralfate (7 percent) on postoperative pain and wound healing after MilliganMorgan's open hemorrhoidectomy through a blinded, prospective, and randomized trial.…”
mentioning
confidence: 99%